Risk of post-operative hemorrhage after adenoidectomy and tonsillectomy: Value of the preoperative determination of partial thromboplastin time and prothrombin time. (January 2019) - Bitar, Mohamad; Dunya, Gabriel; Khalifee, Elie; Muwakkit, Samar; Barazi, Randa
Abstract: Introduction: Tonsillectomy and adenoidectomy (T& A) are the most common pediatric surgical procedures performed world-wide. Bleeding remains the most common complication of these procedures with 1–5.7% prevalence. Methods: We recruited 1269 patients who were scheduled for either tonsillectomy, adenoidectomy or both. All patients had preoperative CBC, PT, and aPTT ordered. According to the results, patients were labelled as either "abnormal group" or "normal group". Results: 35 patients had abnormal lab results 18 of these patients were diagnosed with coagulation disorders on further laboratory testing.9 of these patients had no pertinent history of bleeding. Even though an association is noted between abnormal lab tests and preoperative history of risk of bleeding, the correlation did not have high sensitivity (28.6%). Conclusion: This study provides evidence that preoperative history can give some information on patients with abnormal coagulation profile but may underestimate the prevalence of such diseases. In addition, patients with abnormal coagulation profile have more risk of postoperative bleeding even after adequate medical treatment perioperative. Thus, identifying these patients will help the clinician in providing the best surgical management with the least morbidity and mortality.